Anthropogenic activities control the source dynamics of sediment organic carbon in the lower reach of an inland river. (15th April 2023) - Yang, Changrong; Li, Zhongwu; Wang, Shilan; Ran, Fengwei; Nie, Xiaodong; Liu, Yaojun; Xiao, Tao
Highlights: Sediment organic carbon source undergoes three change periods. The external input of river sediment carbon continues to increase to 82%. The carbon contribution of grassland decreases, while other land types increases. Anthropogenic activities control the sediment organic carbon source of rivers. Abstract: Sediment organic carbon (SeOC) sources with rich information can be used as a "historical archive" reflecting anthropogenic activities in the catchment, which is crucial to carbon management in the watershed. Anthropogenic activities and hydrodynamic conditions significantly influence the river environment and are reflected by the SeOC sources. However, the key drivers of the SeOC source dynamics are ambiguous, which restricts the behavior of regulating the carbon output of the basin. In this study, sediment cores from the lower reach of an inland river were selected to quantify the SeOC sources based on a centennial scale. A partial least squares path model was used to establish the relationship between anthropogenic activities and hydrological conditions with the SeOC sources. Findings showed that the exogenous advantage of SeOC composition was gradually significant (early period: 54.3%; middle period: 81%; later period: 82%) from the bottom layer to the surface layer of the sediments in the lower reach of the Xiangjiang River. Factors related to anthropogenic activities controlled the external input of SeOC (δ 13 C: r∂ = -0.94, P < 0.001; δ 15 N: r∂ = -0.66, P < 0.001). Different anthropogenic activities performed different effects. Land use change aggravated soil erosion and brought more terrestrial organic carbon to the downstream. The variation of grassland carbon input was the most obvious (from 33.6% to 18.4%). In contrast, the reservoir construction intercepted upstream sediments, which might have been the main reason for the slow growth of terrestrial organic carbon input in the downstream in the later period. This study provides a specific grafting for the SeOC records - source changes - anthropogenic activities in the lower reach of the river, which provides scientific basis for watershed carbon management. Graphical abstract: Image, graphical abstract